ANALISIS PENGELOLAAN BARANG MILIK NEGARA (BMN) PADA BADAN PUSAT STATISTIK (BPS) KOTA MAKASSAR - Monik Ajeng Puspitoarum D. W (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to find out and analyze management of state asset in BPS-Statistics of Makassar Regency through planning, implementation and monitoring the state asset. The state asset must be controlled in order to improve public performance of goverment agencies and to minimize the risk of lossing the state asset. Reporting of state asset is a manifestation of the principle of accountability.